Preliminary Phytochemical Screening of Iris Persica L. (Flowers, Leaves, Bulbs and Rhizomes) Collected in Kurdistan Region-Iraq. - M. Amin, Hawraz I.; Amin, Ahmed A.; Hussain, Faiq H.S.; Vidari, Giovanni (Science Journal of University of Zakho, 2016)
The curative properties of medicinal plants are perhaps due to the presence of various secondary metabolites. This paper reports the first investigation of phytochemical constituents present in the methanolic extracts of flowers, leaves, bulbs and rhizomes of Iris persica L. (Iridaceae), collected in Korek Mountain (Rawanduz) in the Kurdistan Region-Iraq, which is used by local people for the treatment of wound inflammation and tumor. The phytochemical analysis was performed to detect the presence of flavonoids, polyphenols, terpenoids, protiens and reducing sugar in all extracts of Iris persica. While tannins and saponins were found in bulb and rhizome extracts only, alkaloids, steroids, aminoacids and anthraquinons were found to be absent in all extracts.